Pathologic Characteristics of Node-Positive Invasive Breast Carcinomas Associated With Extranodal Extension. (21st September 2018) - Wade, Jenna; Little, James; Zhang, Chao; Chen, Zhengjia; Meisel, Jane; Hanley, Krisztina
Abstract: Objectives: Breast cancer is the most common malignancy in women. Extranodal extension (ENE) in nodal metastasis, defined as extension of carcinoma through the nodal capsule into the perinodal adipose tissue, has emerged as an important prognostic factor in various malignancies. Reporting presence and size of ENE in node-positive breast cancer is recommended, as it is associated with increased axillary nodal burden, disease recurrence, and mortality. Association of ENE with various clinicopathologic parameters has not been extensively studied. The aim of this study was to evaluate if the presence of ENE in node-positive breast cancer patients shows any correlation with primary tumor size, histologic type, grade, and hormone receptor status. Methods: This retrospective study focused on patients diagnosed with node-positive invasive breast cancer who also had ENE. For each case, patients' age, tumor size, type, grade, number of positive lymph nodes, presence of ENE, and ER/PR/HER2/Ki-67 status were recorded. These variables were analyzed using the chi-square test for categorical variables and two-sample t test for numerical variables, respectively. Results: Pathologic characteristics of the 211 breast carcinoma cases were as follows: 170 of 211 (80.5%) invasive ductal, 35 of 211 (16.6%) invasive lobular, and 6 of 211 (2.8%) mixed lobular and ductal. Nottingham grades were 24 of 211 (11.4%) grade 1, 106 of 211 (50.23%) grade 2, 63 of 211 (29.8%) grade 3, and 18 of 211 (8.5%) not graded due to neoadjuvant treatment. ENE was present in 162 (76.8%) patients. When tumor parameters were compared between ENE+ and ENE– patients, the variables listed in Table 1 showed statistically significant differences between the two groups. Conclusion: Our study suggests that ENE in node-positive invasive breast carcinoma is more likely to be seen in Her2-negative tumors. Size of primary tumor (T stage) and number of positive lymph nodes also correlate with the presence of ENE.